Critical strategies for construction players in the adoption of biophilic city concept in Malaysia - Khairul Zahreen, Mohd Arof; Syuhaida, Ismail; Chitdrakantan, Subramaniam; Shamila, Azman; Wan Nurul Mardiah, Wan Mohd Rani; Muhammad Farhan, Zolkepli (Malaysian Institute Of Planners, 2020)
Around 2.5 billion individuals will be living in urban areas by 2050. Two out of three individuals are going to live in urban communities or other urban focuses, featuring sustainable urban planning and public services. A biophilic city concept which is a sister term of the green city innately affiliates human being to other living organisms. Apart from adhering to human needs, the concept is the economical among other green city concepts. However, biophilic city concept is still an alien term to construction players and the public. The paper aims to propose and evaluate the critical strategies for construction players in the adoption of the biophilic city concept in Malaysia. 173 respondents consisting of government agencies, developers, consultants and contractors were involved in a questionnaire survey. 81 out of 107 strategies were accepted as the critical strategies in adopting the biophilic city concept. Among the strongest strategies are (1) effective water conservation in biophilic city project; (2) acknowledging biophilic city concept adoption publicly; and (3) adequate material resource availability for the biophilic city project. These strategies fall under three different items, namely; (1) sustainability in the biophilic city project; (2) awards and recognition for biophilic city concept adoption; and (3) organisation in the biophilic city project, respectively. Commitment of all construction players are crucial crucial towards inclusive, sustainable urban planning and public services.